THE TEMPERATURE-DEPENDENT GROWTH MODE OF NICKEL ON THE BASAL-PLANE OF GRAPHITE - Libuda, Jörg; et al. (Surface Science, 1995)
The growth mode of metals on weakly interacting substrates is still a matter of debate. Especially for graphite this question is unsettled. In order to contribute to a clarification, we investigated the temperature dependent growth behaviour of nickel on the basal plane of graphite. Via SPA-LEED (spot profile analysis low energy electron diffraction) we found that Ni(lll) islands are formed at 90 K. The formation of these islands deposited originally at 10(-2) ML/s, however, is a rather slow process, which takes approximately two hours as observed in the profile of the (00) beam. The driving force for this rearrangement taking place after deposition is certainly the small mismatch between the lattice constant of Ni(lll) and the basal plane of graphite. Furthermore, XPS has been used to determine the coverage and the height of the Ni(lll) islands. At 300 K, much larger clusters with a different shape and structure are growing on the surface. It is likely that they represent the thermodynamically stable situation.
Keywords: CARBON; GROWTH; LOW ENERGY ELECTRON DIFFRACTION (LEED); NICKEL; X-RAY PHOTOELECTRON SPECTROSCOPY